A new species of Paracometes Villiers, 1958 from Panama (Coleoptera, Cerambycidae, Disteniinae) - Heffern, Daniel; Santos-Silva, Antonio (Zootaxa, 2016)
Villiers (1958) described Paracometes (Cerambycidae: Disteniinae) for 11 species from Central and South America, and designated Cometes acutipennis Buquet, 1851 as its type species. Santos-Silva and Martins (2004) synonymized Paracometes with Cometes Lepeletier and Audinet-Serville, 1828. Santos-Silva and Tavakilian (2009a) reinstated Paracometes as a distinct genus and provided a new concept for the genus. According to Santos-Silva and Tavakilian (2009b), Paracometes includes six species distributed in Central and South America. The 7th species for this genus is now described.